Superioridad interpretativa del órgano judicial encargado del control de constitucionalidad sobre la potestad que tiene el órgano legislativo (2007)
This essay makes emphasis on the function that our juridical ordering confers the Constitutional Judge by appointing him as the highest and sole interpreter of the Constitution. Likewise, it points out the boundaries which in this regard the Parliament shows.